Embodied arts therapies - Koch, Sabine C.; Fuchs, Thomas (The arts in psychotherapy, 2011)
The body is a particular kind of object. It is the only “thing” that we can perceive from the inside as well as from the outside. For this reason, it is intricately related to the problem of consciousness. This article provides an insight into embodiment approaches as they are emerging in phenomenology and cognitive psychology. The authors introduce important principles of embodiment - unity of body and mind, bidirectionality of cognitive and motor systems, enaction, extension, types of embodiment, relation to empathy -, and connect them with the arts in therapy.
Gesehen am 06.07.2022